Preschool Teachers’ Self-Efficacy in the Teaching of English as a Second Language: Validity and Reliability of Questionnaire - Azman, Noorul Hidayah; Mohamed, Suziyani; Mohamad, Maslawati (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of this study is to determine the validity and reliability of a questionnaire on preschool teachers’ self-efficacy in the teaching of English as a second language in Malaysia. This survey-designed study used questionnaire as the instrument. The questionnaire contains 87 items under three constructs; teachers’ self-efficacy, teachers’ English language proficiency, and teaching strategies. Five experts were involved in validating the questionnaire while the reliability coefficient values were obtained from 200 preschool teachers of three districts. The results have shown that the validity of the questionnaire is high with the coefficient value of .924 based on the consensus from the experts. The Cronbach’s Alpha coefficient values of the reliability for self-efficacy construct was .921, English language proficiency construct was .961, and teaching strategies construct was .976. Therefore, the questionnaire has been proven to have high validity and reliability which is appropriate to measure preschool teachers’ self-efficacy, English language proficiency, as well as teaching strategies in the teaching of English as a second language.